The time is right to introduce an independent commissioner. (2nd January 2021) - Rowland, Andrew; Gerry, Felicity; Proudman, Charlotte; Home, Joseph
Abstract : The authors of Home et al (2020) respond to the Letter to the Editor on the call for an independent anti-female genital mutilation commissioner in the UK